Polymorphism of proinflammatory inerleukin genes in primary open-angle glaucoma - L. Yu. Barycheva; D. M. Kakulia; M. M. Minasyan; V. V. Kuznecova; N. A. Kozmova (Медицинская иммунология, 2024)
Glaucoma is a degenerative disease of the optic nerve, accompanied by the death of retinal ganglion cells (RGCs) and loss of vision. An important role in the pathogenesis of glaucoma is ascribed to activated microglia, which produce pro-inflammatory interleukins and initiate GCS apoptosis. It has been established that single nucleotide polymorphisms of interleukin genes modify the development of neuroinflammation, but their effect on the risk of developing glaucoma is not yet fully established. Our aim was to determine the pathogenetic role of gene polymorphisms in TNFα and IL1β in the development of primary open-angle glaucoma.We have observed 56 patients of Russian nationality from the South of Russia with primary open-angle glaucoma (POAG), 28 patients with stage I, 16 with stage II, 12 with stage III POAG. The single nucleotide polymorphisms TNFα 308G>A (rs1800629) and IL1β -31 Т>С (rs1143627) were studied by restriction fragment analysis of PCR products. The level of pro-inflammatory cytokines (TNFα and IL1β) in the lacrimal fluid of patients with POAG was evaluated by enzyme-linked immunosorbent assay (Vector-Best test system). To perform optical coherence tomography by analysing the thickness of retinal nerve fiber layer (RNFL) with volume and area of the neuroretinal rim using Torson 3D OST 1000 apparatus.Results: in patients with POAG, we have found more common incidence of TNFα 308A (OR = 5.21, p = 0.001), and IL1β-31 T alleles (OR = 1.99, p = 0.04). An increased risk of developing POAG was found in carriers of genotypes 308A/A (OR = 6.30, p = 0.049), 308G/A (OR = 3.60, p = 0.049) and -31T/T (OR = 2.67, p = 0.04). The highest levels of TNFα were determined in the 308A/A group (190 (153.0-220.0) pg/mL), IL1β were in the group (-31) T/T – 6.50 (4.10-7.00) pg/mL. A decreased thickness of the retinal nerve fibers was observed in the patients with TNFα G308A genotype (59.5; 40.0 to 78.0 µm, p = 0.03), and in TNFα A308A carriers (79.0; 65.0 to 80.0 µm, p = 0.001).The TNFα 308 G/A (rs1800629), along with IL1β, -31Т/C (rs1143627) cytokine gene polymorphisms are associated with development of primary open-angle glaucoma. TNFα 308A, IL1β -31T alleles, as well as the 308G/A, 308A/A and -31T/T genotypes seem to be the risk factors for POAG in Russian population. High content of TNFα in the lacrimal fluid was found in the carriers of 308A/A genotype and -31T/T IL1β genotype. The lowest thickness of the retinal nerve fiber layer was observed in the carriers of tTNFα A308A and TNFα G308A genotypes.